4n+34=-2(1-7n)

Simple and best practice solution for 4n+34=-2(1-7n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n+34=-2(1-7n) equation:


Simplifying
4n + 34 = -2(1 + -7n)

Reorder the terms:
34 + 4n = -2(1 + -7n)
34 + 4n = (1 * -2 + -7n * -2)
34 + 4n = (-2 + 14n)

Solving
34 + 4n = -2 + 14n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-14n' to each side of the equation.
34 + 4n + -14n = -2 + 14n + -14n

Combine like terms: 4n + -14n = -10n
34 + -10n = -2 + 14n + -14n

Combine like terms: 14n + -14n = 0
34 + -10n = -2 + 0
34 + -10n = -2

Add '-34' to each side of the equation.
34 + -34 + -10n = -2 + -34

Combine like terms: 34 + -34 = 0
0 + -10n = -2 + -34
-10n = -2 + -34

Combine like terms: -2 + -34 = -36
-10n = -36

Divide each side by '-10'.
n = 3.6

Simplifying
n = 3.6

See similar equations:

| 6t^2=4t+5 | | 0=3x^2-6x+1 | | 12=-4(-7x-3) | | w^2+7w-9=0 | | n-.6n+20000=.15n | | 5xy^5= | | t^2-2t=7 | | w^2=3w+54 | | 400=4t^2+18t | | .50a-3=7-.75a | | 3+4x=3x-7 | | 2(4x+9)=-78 | | (x-2)2+x(x-3)=3(x+4)(x-3)-(x+2)(x-1)+2 | | 3a^3-4a=0 | | 9c^2+6c=0 | | .66x+5=.33x+14 | | 3(8-7x)=-207 | | 4a^3-a=0 | | -5(2x+1)=-45 | | 2(2+5x)=-66 | | 4(2z-2)=7(z-4) | | (8x^3-7x^2+10x-9)-(2x^3-5x^2-8x+9)= | | 13=x+18 | | x^5(2-x)=0.98 | | 6(10+2x)=60 | | 30d^2+37d+10=0 | | -3(-7x+6)=-270 | | 7(3x-7)=-70 | | 7(-6x+4)=-434 | | 7x+5y=10000 | | 9+4m=2m-15 | | 9(4m)=2m-15 |

Equations solver categories